PENGARUH KUALITAS GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (studi empiris pada perusahaan yang termasuk dalam pemeringkatan Corporate Governance Perception Index (CGPI) tahun 2009-2011). - Denta Wisnu Pradipta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research attempts to analyze the effect of Good Corporate Governance (GCG) quality on financial performance. Good Corporate Governance quality is based on the Corporate Governance Perception Index (CGPI) score held by the Indonesian Institute for Corporate Governance (IICG), while the financial performance is measured utilizing Return On Investment dan Total Assets Turnover. The control variable used is the company’s age (AGE), which is the company’s latest annual financial report subtracted by the very first annual financial report since the company has been listed in IDX. This research utilizes double regression analysis for testing the hypothesis which states that Good Corporate Governance (GCG) and financial performance is related using the age of the company (AGE) as the control variable. The result of this research shows that there is a significant relation betweeen Good Corporate Governance quality and Return On Investment and Total Assets Turnover in 2009-2011. Keywords : Good Corporate Governance, Return On Investment, Total Assets Turnover, corporate’s age